PENGARUH TINGKAT PENDIDIKAN, PELATIHAN DAN PENGALAMAN MENGAJAR TERHADAP PROFESIONALISME GURU SMP NEGERI DI KABUPATEN BONE - KASMA WATI (JUPE : Jurnal Pendidikan Mandala, 2021)
This study aims to analyze the influence of education level, training and teaching experience of teachers on the professionalism of SMPN teachers in Bone District. This research was designed using descriptive verification research type. Population in this research is all teachers of SMPN Bone Regency as many as 335 people. Determination of the number of samples is based on the slovin formula and is determined simple randomly. The number of samples based on slovin formula with a tolerance limit of 10%, as many as 77 people . Data were analyzed by multiple linear regression using SPSS 23 software.The results showed that (1) the level of education, training and teaching experience had a positive and significant influence on the professionalism of SMPN teachers in Bone District and (2) The level of education was the most dominant variable affecting the professionalism of SMPN teachers in Bone District